Azerbaijani Engineers in the Global Economy: Transnational Professionals Versus "Button-Pushers". Issue 2 (June 2018) - Sayfutdinova, Leyla; Ergun, Ayça
This article examines the changes in the engineering profession in Azerbaijan after the inflow of foreign investment into Azerbaijan's oil industry since 1990s. The integration of Azerbaijan's oil industry into global economy has led to a significant reshaping of the engineering profession, both within and outside of the oil industry. Multinational companies, which have been the main agents of this integration, have introduced advanced technologies and helped many Azerbaijani engineers to gain access to the international labor market, often serving as credentializing institutions. At the same time, the presence of these multinational companies have also opened the way for new inequalities. They have indirectly created an important division within the engineering profession—a division between internationally mobile engineers from the oil industry and engineers in other industries. Outside of the oil industry, engineering work has in many cases been reduced to routine tasks of assembly and operations, while research, design, and manufacturing were made redundant in the context of the oil-driven development promoted by Azerbaijan's government.